IMPLEMENTASI PROGRAM KELUARGA HARAPAN DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT DI DESA RIMBA SOPING KECAMATAN PADANGSIDIMPUAN ANGKOLA JULU - Ris Artalina Tampubolon; Jenny Yelina ambe; Desy Andarini; Khoirul Kholik Nasution (JURNAL EDUCATION AND DEVELOPMENT, 2024)
The profession of most of the people of Rimba Soping Village is farming. But they do not own their own land or work as farm laborers on other people's land. The increasing cost of living necessities means that many of them still need assistance from the government, such as assistance from the Program Keluarga Harapan (PKH). The aim of the Program Keluarga Harapan (PKH) is to improve the welfare of the people of Rimba Soping Village. The aim of this research is to analyze the implementation of the Program Keluarga Harapan (PKH) in improving the welfare of the community in Rimba Soping Village and what factors hinder the implementation of the Program Keluarga Harapan (PKH). This research uses descriptive research methods with a qualitative approach. The results of this research show that financial assistance from the government has not been completely successful in improving welfare, but on the other hand it can meet the daily needs of the people who receive the Program Keluarga Harapan (PKH) assistance. Factors that hinder the implementation of PKH are the education of the head of the family which is still low, the income earned from working as farmers is still low because they are only farm laborers, population growth is quite high compared to other villages in the same sub-district. Then, the implementation of the Program Keluarga Harapan (PKH) has not gone well, because there are still many obstacles in terms of the accuracy of the nominal amount and the timing of disbursement of funds, as well as assistance for school-age children's education costs not being used optimally.